Progresses and clinical application of super-resolution ultrasound imaging: a narrative review - Jia-yi Gao; Chao Hou (The Ultrasound Journal)
Abstract Microcirculation plays a crucial role in maintaining normal physiological functions in the human body by facilitating the exchange of materials between tissues and blood through a network of microvessels with diameters less than 100 μm. It regulates local hemodynamics and participates in important pathophysiological processes, such as inflammatory reactions and immune responses. In recent years, the monitoring of super-resolution ultrasound (SRUS) in microcirculation has significantly enhanced our understanding of microvascular structure and function, while also providing insights into the noninvasive evaluation of organ conditions at the micro-level, thereby promoting the diagnosis and treatment of related diseases. This review summarizes the development and clinical application progress of SRUS, offering valuable insights into future research directions.